Arbitration in Indian public service - Bhaskara Rao V.
Tracing the origin and growth of arbtration in India public service.The author elaborates on Joint Consultative Machinery and Compulsory Arbitration (JCM) Scheme. He discusses JCMs scope, structure and process - covering negoliation, conciliation, adjudication, grant of award and its implementation. He also attempts an assessment of JCMs contribution to civil service staff relations in government
Keywords: Public Service -- India; Arbitration (Administrative Law) -- India; Civil Service -- India; Civil Service